How does the hydrophobic content of methacrylate ABA triblock copolymers affect polymersome formation?. Issue 15 (14th June 2021) - Zhang, Xinmo; Contini, Claudia; Constantinou, Anna P.; Doutch, James J.; Georgiou, Theoni K.
Abstract: Polymersomes are exciting self‐assembled structures with great potential in pharmaceutical applications. A systematic investigation of a novel series of methacrylate‐based polymersomes is reported in this study. Five well‐defined ABA triblock copolymers with A being based on tri(ethylene glycol) methyl methacrylate and B being based on 2‐(diethylamino)ethyl methacrylate (DMAEMA) were synthesized using a living polymerization method. The effect of the composition of the ABA triblock copolymers on the thickness of the hydrophobic membrane of the polymersomes and the release of a model drug is demonstrated. Abstract :